KEBIJAKAN FORMULASI KEADILAN RESTORATIF DALAM SISTEM PERADILAN PIDANA ANAK - I Made Wahyu Chandra Satriana (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2013)
The discussion on this journal raised regarding policy formulation RestorativeJustice in the Criminal Justice System Children . The objectives of this research thatin order to properly analyze the basic ideas contained in restorative justice , to dowith children in conflict with the law and to analyze policy formulation set forth in the Law. 112012 on the Criminal Justice System Kids for restorative justice to children inconflict with the law . While this type of research used in scientific journals this isthe kind of normative legal research , because it is based on the assessment thatthere is a conflict between the norms of Law. 11 of 2012 on the Criminal JusticeSystem Children with the norms contained in the draft - Criminal Code ( CriminalCode ) . In this case the unlawful act committed by the child who has not reached theage of 18 (eighteen years ) diversion efforts which have the purpose for the creationof a balance between the interests of focus and attention to the perpetrator and thevictim also impact the completion of the criminal case that happens in thecommunity to ensure and protecting children and their rights in order to live , grow,develop and participate optimally in accordance with the dignity of humanity , aswell as protection from violence and discrimination .